Quantitative elucidation of the elusive role of defects in polycrystalline MFI zeolite membranes on xylene separation performance - Hong, Sungwon; Kim, Dongjae; Richter, Hannes; Moon, Jong-Ho; Choi, Nakwon; Nam, Jaewook; Choi, Jungkyu (ELSEVIER SCIENCE BV, 2019)
The defect structure in a c-out-of-plane oriented MFI membrane was quantitatively analyzed by processing images obtained by fluorescence confocal optical microscopy (FCOM). The MFI membranes were placed in contact with a dye solution at a fixed concentration (1 mM) for 2, 4, and 8 d and at different concentrations (0.01, 0.1, and 1 mM) for 8 d. This approach led to the identification and understanding of two types of defects (cracks and grain boundary defects). The representative quantitative properties (porosity and tortuosity) relevant to the defects were obtained via the image processing. Furthermore, the estimation of the defect sizes was complemented by the use of a one-dimensional permeation model for the molar flux of the p-/o-xylene components across the c-oriented MFI membrane. Using this combination, we found that although the amount of defects in the whole zeolite membrane was close to similar to 1%, they provided non-selective, facile pathways that accounted for similar to 58% of the total molar flux of faster permeating p-xylene. Surprisingly, despite the lower density (pixel-based area fraction) of cracks, wider cracks (similar to 7.8-8.2 nm) accounted for the much higher molar flux of permeation components compared to major, but narrower grain boundary defects (similar to 1-2 nm). Indeed, the cracks mainly deteriorated a p-/o-xylene separation performance of the c-oriented MFI membrane. Finally, we found that the crack size increased in the presence of p-xylene so that the molar flux of o-xylene in the binary mixture was significantly increased, thus reducing the p-/o-xylene separation performance. This behavior was ascribed to the flexible MFI zeolite structure after the adsorption of p-xylene.
Keywords: SCANNING CONFOCAL MICROSCOPY; SECONDARY SEEDED GROWTH; ORIENTED SILICA MFI; HIGH-FLUX; ZSM-5 MEMBRANES; GAS SEPARATION; HIGH-PRESSURE; PERVAPORATION; DEPOSITION; MIXTURES